2022
DOI: 10.1016/j.anai.2021.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Asthma in older adults with severe coronavirus disease 2019

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
1
0
5
Order By: Relevance
“…Изучение данных показал, что COVID19 сопровож дался тяжелым течением сопутствующего заболе вания примерно у 23% пациентов и для 6% из них закончился летально. Лица с тяжелыми сопутству ющими заболеваниями были значительно старше (средний возраст -60,4 года; 95% ДИ: 57,8-63,1), чем пациенты, не имеющие тяжелых заболеваний (44,6 года; 95% ДИ: 42,8-46,3, Р < 0,0001).…”
Section: Reviewunclassified
See 1 more Smart Citation
“…Изучение данных показал, что COVID19 сопровож дался тяжелым течением сопутствующего заболе вания примерно у 23% пациентов и для 6% из них закончился летально. Лица с тяжелыми сопутству ющими заболеваниями были значительно старше (средний возраст -60,4 года; 95% ДИ: 57,8-63,1), чем пациенты, не имеющие тяжелых заболеваний (44,6 года; 95% ДИ: 42,8-46,3, Р < 0,0001).…”
Section: Reviewunclassified
“…В период начала пандемии COVID19 россий ские ученые проводили исследование, в котором изучалось течение COVID19 у пожилых пациентов старше 65 лет, длительно страдавших бронхиаль ной астмой. В ходе исследования выяснилось, что неаллергический фенотип астмы, тяжесть астмы, системное применение стероидов и сопутствующие заболевания могут быть факторами риска неблаго приятных исходов у пожилых пациентов с астмой и тяжелой формой COVID19 [44].…”
Section: Sarscov2 и бронхиальная астмаunclassified
“…во время госпитализации по сравнению с группой выживших: 60% [36-80] (n = 9) против 5% [2][3][4][5][6][7][8][9][10][11] (n = 4), p < 0,001. Также был проведен анализ распространенности сопутствующих заболеваний в группах исследования (рис.…”
Section: Covid-19unclassified
“…В исследованиях представлены многочисленные факторы, которые могут играть роль в восприимчивости и тяжести COVID-19 у пациентов с БА [8]. Они включают в себя тяжесть самой астмы, ее фенотип (аллергический или неаллергический), лечение (принимаются системные кортикостероиды или нет), сопутствующие заболевания и возраст [9][10][11][12][13].…”
Section: Introductionunclassified
“…In this process, it has been suggested that the asthma phenotype produces different responses to a SARS-CoV-2 infection. There are studies which find a better prognosis or lower risk of disease for patients with the T2 versus the non-T2 phenotype, in patients with early-onset versus late-onset asthma, and in allergic versus non-allergic patients [ 15 17 ].…”
mentioning
confidence: 99%